Electrolyte and lithium ion battery

By using an electrolyte containing lithium difluorosulfonimide, rich in single pairs of P and O atomic compounds and vinylene carbonate in lithium-ion batteries, the problem of thermal runaway at high temperatures of lithium-ion batteries is solved, significantly improving the battery's high-temperature storage performance and thermal stability, and improving the battery's safety.

CN119725755AInactive Publication Date: 2025-03-28GUANGZHOU TINCI MATERIALS TECH

Patent Information

Application Number
CN202510214559.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Lithium-ion batteries are prone to thermal runaway at high temperatures, leading to safety issues such as fires and explosions. The existing electrolyte cannot effectively improve the high-temperature storage performance and thermal stability of lithium-ion batteries.

Method used

An electrolyte containing lithium difluorosulfonimide, a first additive and a second additive is used. The first additive is rich in single pairs of P and O atoms and Lewis basic P-N bonds, and has the ability to scavenge free radicals, Lewis acid and HF. The second additive is vinylene carbonate, which is used to stabilize the SEI membrane.

Benefits of technology

Through synergistic action, the first additive and the second additive significantly improve the high-temperature storage performance and thermal stability of the lithium-ion battery, reduce the heat generated by the reaction, and improve the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725755A_ABST
    Figure CN119725755A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte and a lithium ion battery. The electrolyte comprises a solvent, additives and lithium salt, the lithium salt comprises lithium bis (fluorosulfonyl) imide, the additives comprise a first additive and a second additive, the first additive is selected from a compound shown in the formula I, and the second additive is selected from vinylene carbonate. The first additive and the second additive have a synergistic effect, so that the high-temperature storage performance and the thermal stability of the lithium ion battery are improved. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to an electrolyte and a lithium-ion battery. Background Art

[0002] Lithium-ion batteries (LIBs) have developed rapidly in the fields of 3C equipment, electric vehicles, and energy storage. However, the safety issues such as fire and explosion brought by LIBs have gradually attracted social attention. In particular, the development trend of large-capacity and large-size batteries such as 280 Ah has aggravated the occurrence of accidents. Among them, thermal runaway (TR) is a common and key cause of LIBs safety issues. When the heat generation rate in LIBs is greater than the heat dissipation rate, TR will be triggered, and the reaction will spontaneously increase the temperature of LIBs. At relatively high temperatures, severe redox exothermic reactions may be triggered, generating a large amount of heat and running out of control, leading to danger. Therefore, removing or reducing the main exothermic reactions during the evolution of TR is crucial to ensure the safety of LIBs.

[0003] As the conductive carrier of ions between the positive and negative electrodes of secondary batteries, the electrolyte is critical to the performance of secondary batteries. Therefore, it is urgent to develop more comprehensive electrolytes to improve the high-temperature storage performance and thermal stability of lithium-ion batteries. Summary of the invention

[0004] The purpose of this application is to provide an electrolyte and a lithium-ion battery to improve the high-temperature storage performance and thermal stability of the lithium-ion battery. The specific technical solution is as follows:

[0005] The first aspect of the present application provides an electrolyte, which includes a solvent, an additive and a lithium salt; the additive includes a first additive and a second additive;

[0006] The first additive is selected from the compound shown in formula I;

[0007] Wherein, R1 and R2 are independently selected from unsubstituted or fluorine-substituted C1-C5 alkyl, unsubstituted or fluorine-substituted C2-C4 alkenyl; the mass percentage of the first additive in the electrolyte is A, 0.1%≤A≤8%, preferably 0.1%≤A≤3%;

[0008] The second additive is selected from vinylene carbonate (VC); the mass percentage of the second additive in the electrolyte is B, 0.1%≤B≤5%, preferably 1%≤B≤2.5%;

[0009] The lithium salt includes lithium bis(fluorosulfonyl)imide; the mass percentage of the lithium bis(fluorosulfonyl)imide in the electrolyte is C1, 10%≤C1≤20%.

[0010] In one embodiment of the present application, the compound represented by formula I is selected from at least one of the following compounds: .

[0011] In one embodiment of the present application, the lithium salt also includes an auxiliary salt; the auxiliary salt is selected from at least one of LiPF6, LiSO3CF3, LiBF4, LiN(SO2CF3)2, LiPO2F2, LiPF2(C2O4)2 and LiPF4C2O4; the mass percentage of the auxiliary salt in the electrolyte is C2, 0.1%≤C2≤2%.

[0012] In one embodiment of the present application, the solvent is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate and methyl propyl carbonate; the mass percentage of the solvent in the electrolyte is D, 65%≤D≤89%.

[0013] The second aspect of the present application provides a lithium-ion battery, which includes a positive electrode plate, a negative electrode plate, a separator and the electrolyte described in the first aspect of the present application.

[0014] In one embodiment of the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes graphite.

[0015] In one embodiment of the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer arranged on at least one surface of the positive electrode current collector, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material is selected from at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium nickel cobalt manganese oxide, lithium cobalt oxide and lithium-rich manganese-based materials. Preferably, the positive electrode active material is selected from lithium iron phosphate.

[0016] Beneficial effects of this application:

[0017] The present application provides an electrolyte and a lithium ion battery. The electrolyte of the present application includes a solvent, an additive and a lithium salt, wherein the lithium salt includes lithium bis(fluorosulfonyl)imide (LiFSI), and the additive includes a first additive and a second additive, wherein the first additive is selected from the compound shown in formula I, wherein the compound shown in formula I is rich in a single pair of P and O atoms and a Lewis basic PN bond, and has the ability to remove free radicals, Lewis acids and HF. LiFSI reacts with lithiated graphite (LiC6) at about 210°C to break the NS bond of LiFSI, release a large number of free radicals, and produce a violent exothermic reaction. Since the outer layer of the sulfur atom has an empty orbital, these empty orbitals can be used to accept an external electron cloud, thereby making the sulfur atom a Lewis acid. After the compound shown in formula I is introduced, the Lewis basic PN bond in the compound shown in formula I can combine with the Lewis acid to slow down the generation of reaction heat. In lithium ion batteries, the thermal stability can be effectively improved, the heat generated by the reaction can be reduced, and the temperature at which the reaction occurs can be increased, thereby improving the safety of the battery. The reduction of cyclic phosphoric acid in the compound shown in Formula I also helps to form a functional solid electrolyte interface (SEI) film on the negative electrode, so the use of additives with this structure can improve the safety of lithium-ion batteries. The introduction of the second additive makes the formed SEI film more stable, making the SEI layer rich in carbonates and phosphates, and having good thermal stability, thereby inhibiting the exothermic reaction between LiFSI and the negative electrode. In short, the electrolyte additive of the present application includes a first additive and a second additive, the two additives are used in combination, and the mass percentage of the first additive and the second additive in the electrolyte is limited to the scope of the present application. The two work synergistically to make the SEI layer rich in non-single carbonate or phosphate components, which can effectively improve the high temperature storage performance and thermal stability of lithium-ion batteries.

[0018] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and a person skilled in the art can also obtain other embodiments based on these drawings.

[0020] Figure 1 The differential scanning calorimetry (DSC) exothermic test curves of Examples 1-3 of the present application are shown. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0022] In a first aspect, the present application provides an electrolyte, which includes a solvent, an additive and a lithium salt; the additive includes a first additive and a second additive;

[0023] The first additive is selected from the compound shown in formula I;

[0024] Wherein, R1 and R2 are independently selected from unsubstituted or fluorine-substituted C1-C5 alkyl, unsubstituted or fluorine-substituted C2-C4 alkenyl; the mass percentage of the first additive in the electrolyte is A, 0.1%≤A≤8%, preferably 0.1%≤A≤3%; the second additive is selected from vinylene carbonate; the mass percentage of the second additive in the electrolyte is B, 0.1%≤B≤5%, preferably 1%≤B≤2.5%. For example, the mass percentage A of the first additive in the electrolyte can be 0.1%, 0.5%, 1%, 3%, 5%, 8% or a range consisting of any two of the values; the mass percentage B of the second additive in the electrolyte can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5% or a range consisting of any two of the values. The mass percentages of the first additive and the second additive in the electrolyte, respectively, within the scope of this application, can improve the high temperature storage performance and thermal stability of lithium-ion batteries;

[0025] The lithium salt includes lithium bis(fluorosulfonyl)imide; the mass percentage of the lithium bis(fluorosulfonyl)imide in the electrolyte is C1, 10%≤C1≤20%. For example, the mass percentage C1 of the lithium bis(fluorosulfonyl)imide in the electrolyte may be 10%, 12%, 14%, 16%, 18%, 20%, or a range consisting of any two of these values.

[0026] It was found in the study that although lithium bis(fluorosulfonyl)imide has good thermal stability itself, it will react with the charged negative electrode in the battery to release a large amount of heat, causing thermal runaway, and become the "initiator and accelerator" of the substance-energy conversion reaction that triggers the thermal runaway of the battery. The electrolyte of the present application includes lithium bis(fluorosulfonyl)imide, and the mass percentage of lithium bis(fluorosulfonyl)imide in the electrolyte is regulated within the scope of the present application. By introducing the compound shown in formula I, the compound shown in formula I is rich in a single pair of P and O atoms and a Lewis basic PN bond, and has the ability to scavenge free radicals, Lewis acids and HF, the safety of the battery can be improved. At the same time, the reduction of cyclic phosphoric acid in the compound shown in formula I helps to form a functional SEI film on the negative electrode. The introduction of the second additive makes the formed SEI film more stable, thereby inhibiting the exothermic reaction of lithium bis(fluorosulfonyl)imide and the negative electrode. In summary, the electrolyte of the present application has good thermal stability, can effectively alleviate the evolution process of thermal runaway of the battery, inhibit the exothermic reaction, and can effectively improve the high temperature storage performance and thermal stability of lithium-ion batteries.

[0027] In one embodiment of the present application, the compound represented by formula I is selected from at least one of the following compounds:

[0028] Among them, the CAS number of the compound represented by formula I-1 is 7114-67-2, and the CAS number of the compound represented by formula I-2 is 2923203-78-3.

[0029] In one embodiment of the present application, the lithium salt also includes an auxiliary salt; the auxiliary salt is selected from at least one of LiPF6, LiSO3CF3, LiBF4, LiN(SO2CF3)2, LiPO2F2, LiPF2(C2O4)2 and LiPF4C2O4; the mass percentage of the auxiliary salt in the electrolyte is C2, 0.1%≤C2≤2%. For example, the mass percentage C2 of the auxiliary salt in the electrolyte can be 0.1%, 0.5%, 1%, 1.5%, 2% or a range consisting of any two of the values. The electrolyte includes the above-mentioned auxiliary salt and regulates the mass percentage of the auxiliary salt in the electrolyte within the scope of the present application, which can make the electrolyte have higher ionic conductivity and good electrochemical stability, and can further improve the high temperature storage performance and thermal stability of the lithium-ion battery.

[0030] In one embodiment of the present application, the solvent is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate and methyl propyl carbonate; the mass percentage of the solvent in the electrolyte is D, 65%≤D≤89%. For example, the mass percentage D of the solvent in the electrolyte can be 65%, 70%, 75%, 80%, 85%, 89% or a range consisting of any two of these values. The electrolyte includes the above-mentioned solvents, and the mass percentage of the solvent in the electrolyte is regulated within the scope of the present application, so that the electrolyte has a suitable viscosity, a high ionic conductivity and good electrochemical stability, which can further improve the high temperature storage performance and thermal stability of the lithium-ion battery.

[0031] The present application has no particular restrictions on the preparation method of the electrolyte, as long as the purpose of the present application can be achieved. For example, various solvents in the electrolyte can be mixed, and then lithium salts and additives can be added and mixed evenly.

[0032] The second aspect of the present application provides a lithium-ion battery, which includes a positive electrode plate, a negative electrode plate, a separator and the electrolyte described in the first aspect of the present application.

[0033] In one embodiment of the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes graphite.

[0034] The present application does not specifically limit the type of graphite, as long as it can achieve the purpose of the present application. For example, it can be selected from natural graphite or artificial graphite. Considering the cost issue, the current commercial lithium-ion batteries are still mainly based on graphite negative electrodes. In order to achieve better cycle performance, more LiFSI will be introduced into lithium-ion batteries to improve battery performance. After the lithium-ion battery is charged, the negative electrode graphite is embedded with lithium to become LiC6. When LiFSI decomposes under high temperature (about 330°C) to produce violent heat release, and when there is electricity, LiFSI and LiC6 react in advance at about 210°C, and huge heat is generated in the lithium-ion battery, resulting in severe thermal runaway. Using the electrolyte provided by the present application, the compound shown in Formula I is rich in a single pair of P and O atoms and Lewis basic PN bonds, and has the ability to scavenge free radicals, Lewis acids and HF. In lithium-ion batteries, it can effectively improve thermal stability, reduce the heat generated by the reaction of LiFSI and LiC6, and increase the temperature of the reaction, thereby improving the safety of the battery; the reduction of cyclic phosphate in the compound shown in Formula I helps to form a functional SEI film on the negative electrode, and the introduction of the second additive makes the formed SEI film more stable, thereby inhibiting the exothermic reaction of the negative electrode, effectively reducing the reaction heat of LiFSI and LiC6, and reducing the danger of thermal runaway to a certain extent, thereby improving the high temperature storage performance and thermal stability of the lithium-ion battery.

[0035] The above-mentioned "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its thickness direction, or on two surfaces of the negative electrode current collector along its thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the negative electrode current collector, or it can be a partial area of ​​the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.

[0036] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam or copper foam may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).

[0037] The present application has no particular limitation on the thickness of the negative electrode material layer and the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided negative electrode material layer is 30 μm to 70 μm, and the thickness of the negative electrode current collector is 3 μm to 10 μm.

[0038] In one embodiment of the present application, the negative electrode material layer may further include a conductive agent and a binder. The present application does not particularly limit the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of superconducting carbon black (Super P), acetylene black, Ketjen black, carbon nanotubes, graphene and carbon fibers. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The binder may include but is not limited to at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), lithium polyacrylate (PAALi), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent and the binder in the negative electrode material layer. Those skilled in the art may select according to actual needs as long as the purpose of the present application can be achieved.

[0039] In one embodiment of the present application, the negative electrode material layer may further include a thickener, which may include but is not limited to at least one of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose. The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent, the binder, and the thickener in the negative electrode material layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.

[0040] Optionally, the negative electrode plate may further include a conductive layer, and the conductive layer is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, and it may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, and it may be at least one of the above conductive agent and the above binder.

[0041] In some embodiments of the present application, the surface density of the negative electrode material layer is 5 mg / cm 2 ~12mg / cm 2 .

[0042] The present application has no particular restrictions on the preparation method of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, graphite, conductive agent, thickener and binder can be mixed in a certain proportion, deionized water can be added and stirred evenly to obtain a negative electrode slurry with a solid content of 45wt% to 70wt%. The negative electrode slurry is evenly coated on one surface of the negative electrode collector, and after drying, a negative electrode sheet coated with a negative electrode material layer on one side is obtained. Then, the above coating steps are repeated on the other surface of the negative electrode collector, and after drying, a negative electrode sheet coated with a negative electrode material layer on both sides is obtained, which is cold pressed, rolled, trimmed, cut, and striped. After stripping, it is dried under vacuum conditions, and the pole ears are welded to obtain a negative electrode sheet.

[0043] In one embodiment of the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer arranged on at least one surface of the positive electrode current collector, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material is selected from at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523), lithium cobalt oxide and lithium-rich manganese-based materials; preferably, the positive electrode active material is selected from lithium iron phosphate.

[0044] The above-mentioned “positive electrode material layer disposed on at least one surface of the positive electrode current collector” means that the positive electrode material layer can be disposed on one surface of the positive electrode current collector along its thickness direction, or on two surfaces of the positive electrode current collector along its thickness direction. It should be noted that the “surface” here can be the entire area of ​​the surface of the positive electrode current collector, or a partial area of ​​the surface of the positive electrode current collector. This application is not particularly limited, as long as the purpose of this application can be achieved.

[0045] The present application has no particular restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the positive electrode current collector can be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil, aluminum alloy foil, nickel foil or nickel alloy can be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).

[0046] The present application has no particular limitation on the thickness of the positive electrode material layer and the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided positive electrode material layer is 50 μm to 250 μm, and the thickness of the positive electrode current collector is 7 μm to 20 μm.

[0047] In one embodiment of the present application, the positive electrode material layer may also include a conductive agent and a binder. The present application does not particularly limit the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of superconducting carbon black (Super P), acetylene black, Ketjen black, carbon nanotubes, graphene and carbon fibers. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The binder may include but is not limited to at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. The present application does not particularly limit the mass ratio of the positive active material, the conductive agent and the binder in the positive electrode material layer. Those skilled in the art may select according to actual needs as long as the purpose of the present application can be achieved.

[0048] Optionally, the positive electrode sheet may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited, and it can be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, for example, it can be at least one of the above conductive agent and the above binder.

[0049] The present application has no particular restrictions on the preparation method of the positive electrode sheet, as long as the purpose of the present application can be achieved, for example, the positive electrode active material, the conductive agent, and the binder are mixed in a certain proportion, N-methylpyrrolidone (NMP) is added and stirred evenly, and a positive electrode slurry with a solid content of 50wt% to 85wt% is obtained. The positive electrode slurry is evenly coated on one surface of the positive electrode collector, and a positive electrode sheet coated with a positive electrode material layer on one side is obtained after drying. Then the above coating steps are repeated on the other surface of the positive electrode collector, and a positive electrode sheet coated with a positive electrode material layer on both sides is obtained after drying. After cold pressing, rolling, trimming, cutting, slitting, and drying under vacuum conditions after slitting, the pole ears are welded to obtain a positive electrode sheet.

[0050] The present application has no particular restrictions on the separator, as long as the purpose of the present application can be achieved. For example, the material of the separator can be selected from but not limited to at least one of polyethylene (PE), polypropylene (PP), glass fiber, polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI) and polyamide (PA). The type of the separator can include at least one of a woven membrane, a non-woven fabric, a microporous membrane, a composite membrane, a rolled membrane and a spun membrane.

[0051] In the present application, there is no particular limitation on the thickness of the separator as long as the purpose of the present application can be achieved. For example, the thickness of the separator may be 4 μm to 20 μm.

[0052] In the present application, the lithium-ion battery also includes a shell for accommodating a positive electrode plate, a separator, a negative electrode plate and an electrolyte, as well as other components known in the field of lithium-ion batteries, and the present application does not limit the above-mentioned other components. The present application has no special restrictions on the shell, and it can be a shell known in the art, as long as the purpose of the present application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal, and the present application does not limit the type of metal. A metal hard shell known in the art can be used, as long as the purpose of the present application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.

[0053] The preparation process of the lithium-ion battery of the present application is well known to those skilled in the art and is not particularly limited in the present application. For example, the preparation process of the lithium-ion battery may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.

[0054] Example

[0055] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.

[0056] Test methods and equipment:

[0057] High temperature storage performance test

[0058] Place the lithium-ion battery in a 25℃ constant temperature box and let it stand for 24 hours. Then charge the lithium-ion battery at a constant current of 1C to a voltage of 3.65V, then charge it at a constant voltage of 3.65V to a current of 0.05C, then discharge it at a constant current of 1C to a voltage of 2.00V, record the initial discharge capacity as Q1, test the initial thickness of the lithium-ion battery D1, then charge the lithium-ion battery at a constant current of 1C to a voltage of 3.65V, then charge it at a constant voltage of 3.65V to a current of 0.05C. 5C, then place the lithium-ion battery in a 45℃ explosion-proof oven, store it for 30 days, test the battery thermal thickness D2 in the oven, then take out the lithium-ion battery and cool it to room temperature, at 25℃, discharge the lithium-ion battery at a constant current of 1C to a voltage of 2.00V, record the discharge capacity at this time as Q2, then charge the lithium-ion battery at a constant current of 1C to a voltage of 3.65V, and then charge it at a constant voltage of 3.65V to a current of 0.05C, record the charging capacity at this time as Q3.

[0059] Storage thickness expansion rate (%) = (D2-D1) / D1×100%;

[0060] Storage capacity retention rate (%) = Q2 / Q1×100%;

[0061] Storage capacity recovery rate (%) = Q3 / Q1×100%;

[0062] The high-temperature storage performance of lithium-ion batteries is evaluated by the storage thickness expansion rate, storage capacity retention rate and storage capacity recovery rate. The smaller the storage thickness expansion rate and the larger the storage capacity retention rate and storage capacity recovery rate, the better the high-temperature storage performance of the lithium-ion battery.

[0063] Heat release test

[0064] The lithium-ion battery was placed in a 25°C constant temperature box for 24 hours, charged at a constant current of 0.1C for 6 hours to 50% state of charge (SOC) for formation, and then charged at a constant current of 0.2C to 100% SOC, then discharge at a constant current of 1C to a voltage of 2.00V, then charge the lithium-ion battery at a constant current of 1C to a voltage of 3.65V, and then charge at a constant voltage of 3.65V to a current of 0.05C, and then discharge at a constant current of 1C to a voltage of 2.00V, then charge the lithium-ion battery at a constant current of 1C to a voltage of 3.65V, and then charge at a constant voltage of 3.65V to a current of 0.05C, and then discharge at a constant current of 1C to a voltage of 2.00V, then charge the lithium-ion battery at a constant current of 1C to a voltage of 3.65V, and then charge at a constant voltage of 3.65V to a current of 0.05C, so that the lithium-ion battery reaches a fully charged state, test the capacity of the lithium-ion battery after capacity division, and then disassemble the fully charged battery after capacity division, and take out the negative electrode sheet. Weigh 5 mg of the negative electrode, add 3 μL of electrolyte and prepare the sample with a high-pressure crucible (Netzsch high-pressure crucible (27 μL)), and then perform differential scanning calorimetry (DSC) test. The test instrument model is Netzsch DSC 214. Among them, the temperature rise range is 25℃~400℃, and the heating rate is 10℃ / min. Then record the main exothermic peak temperature, that is, the point where the main exothermic reaction occurs, and calculate the peak area to obtain the heat release. The larger the value of the main exothermic peak temperature, the higher the temperature point at which thermal runaway occurs, and the later the point at which thermal runaway occurs.

[0065] Example 1-1

[0066] <Preparation of Electrolyte>

[0067] In an argon atmosphere glove box (water content <10ppm, oxygen content <1ppm), ethylene carbonate (EC), propylene carbonate (PC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 32:4:46.9 to obtain a base solvent, and lithium bis(fluorosulfonyl)imide (LIFSI) is added, and then a first additive (the compound shown in Formula I-1) and a second additive (VC) are added to the base solvent, dissolved and mixed to obtain an electrolyte; wherein, based on the mass of the electrolyte, the mass percentage C1 of LIFSI is 15%, the mass percentage A of the first additive is 0.1%, the mass percentage B of the second additive is 2%, and the balance is the base solvent.

[0068] <Preparation of positive electrode sheet>

[0069] The positive electrode active material lithium iron phosphate (LFP), the binder polyvinylidene fluoride (PVDF), and the conductive agent superconducting carbon black (Super P) were mixed in a mass ratio of 96:2:2, N-methylpyrrolidone (NMP) was added, and the mixture was stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 55wt%; the positive electrode slurry was evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 17μm, and after drying at 85°C, a positive electrode sheet with a single-sided positive electrode material layer coated with a coating thickness of 79μm was obtained; the above steps were repeated on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet with a double-sided positive electrode material layer coated; after drying at 85°C, the positive electrode sheet was cold pressed, rolled, trimmed, cut, and slit, and after slit, it was dried at 85°C for 4 hours under vacuum conditions, and the pole ears were welded to obtain a positive electrode sheet with a specification of 540mm×55mm; wherein the surface density of the positive electrode material layer is 17.5mg / cm 2 .

[0070] <Preparation of negative electrode sheet>

[0071] The negative electrode active material artificial graphite (Bai Te Rui), the conductive agent superconducting carbon black (Super P), the thickener sodium carboxymethyl cellulose (CMC) and the binder styrene butadiene rubber (SBR) are mixed in a mass ratio of 95:1.5:1.5:2, deionized water is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry with a solid content of 49wt%; the negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 9μm, and after drying at 85°C, a negative electrode sheet with a single-sided coating of a negative electrode material layer with a coating thickness of 49.5μm is obtained; the above steps are repeated on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet with a double-sided coating of a negative electrode material layer; after drying at 85°C, the negative electrode sheet is cold pressed, rolled, trimmed, cut, and slit, and after slit, it is dried at 85°C for 4 hours under vacuum conditions, and the pole ears are welded to obtain a negative electrode sheet with a specification of 660mm×59mm; wherein the surface density of the negative electrode material layer is 8mg / cm 2 .

[0072] <Preparation of Separator>

[0073] A polypropylene porous membrane with a thickness of 16 µm was used as the separator.

[0074] <Preparation of lithium-ion batteries>

[0075] The positive electrode sheet, separator and negative electrode sheet prepared above are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the electrode assembly is wound. The electrode assembly is placed in an aluminum plastic film packaging bag, and the water is removed at 85°C, and the electrolyte prepared above is injected, and the injection coefficient is 4.5g / Ah. After vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained. Among them, the standing time is 24 hours, the forming current is 0.05C, the upper limit voltage of the forming is 3.65V, and the forming temperature is 45°C.

[0076] Example 1-2 to Example 1-10

[0077] Except that the mass percentage of the first additive and the second additive is adjusted according to Table 1 in <Preparation of Electrolyte>, the mass percentage of the base solvent is changed accordingly (when the mass percentage of the first additive and the second additive increases / decreases, the corresponding EMC content is reduced / increased at the same time), and the percentage of other components in the electrolyte remains unchanged, the rest is the same as Example 1-1. Among them, the differential scanning calorimetry (DSC) exothermic test curve of Example 1-3 is as follows Figure 1 shown.

[0078] Embodiment 1-11

[0079] Except that the type of the first additive in <Preparation of Electrolyte> was adjusted according to Table 1, the rest was the same as Example 1-3.

[0080] Example 2-1 to Example 2-3

[0081] Except that the auxiliary salt is added and its mass percentage is adjusted according to Table 2 in <Preparation of Electrolyte>, the mass percentage of the base solvent is changed accordingly (when the mass percentage of the auxiliary salt increases, the corresponding EMC content is reduced at the same time), and the percentages of other components in the electrolyte remain unchanged, the rest are the same as Examples 1-3.

[0082] Example 2-4 to Example 2-9

[0083] Except for adjusting the type of auxiliary salt according to Table 2 in <Preparation of Electrolyte>, the rest is the same as Example 2-2.

[0084] Comparative Example 1-1

[0085] The method is the same as Example 1-1 except that the first additive and the second additive are not added in <Preparation of Electrolyte>, the mass percentage of the base solvent is changed accordingly (when the first additive and the second additive are not included, the corresponding EMC content is increased), and the percentages of other components in the electrolyte remain unchanged.

[0086] Comparative Example 1-2

[0087] Except that the second additive is not added in <Preparation of Electrolyte>, the mass percentage of the base solvent changes accordingly (when the mass percentage of the second additive decreases, the corresponding EMC content is increased at the same time), and the percentages of other components in the electrolyte remain unchanged, the rest are the same as Examples 1-3.

[0088] Comparative Examples 1-3

[0089] Except that the first additive is not added in <Preparation of Electrolyte>, the mass percentage of the base solvent changes accordingly (when the mass percentage of the first additive decreases, the corresponding EMC content is increased at the same time), and the percentages of other components in the electrolyte remain unchanged, the rest are the same as Examples 1-3.

[0090] Comparative Examples 1-4

[0091] The preparation method is the same as Example 1-1 except that the second additive is not added in <Preparation of Electrolyte>, the mass percentage of the first additive is adjusted according to Table 1, the mass percentage of the base solvent is changed accordingly (when the mass percentage of the first additive and the second additive increases / decreases, the corresponding EMC content is reduced / increased at the same time), and the percentage of other components in the electrolyte remains unchanged.

[0092] Comparative Examples 1-5

[0093] The preparation method is the same as Example 1-1 except that the first additive is not added in <Preparation of Electrolyte>, the mass percentage of the second additive is adjusted according to Table 1, the mass percentage of the base solvent is changed accordingly (when the mass percentage of the first additive and the second additive increases / decreases, the corresponding EMC content is reduced / increased at the same time), and the percentage of other components in the electrolyte remains unchanged.

[0094] Comparative Examples 1-6 to Comparative Examples 1-9

[0095] Except that the mass percentage of the first additive and the second additive is adjusted according to Table 1 in <Preparation of Electrolyte>, the mass percentage of the base solvent changes accordingly (when the mass percentage of the first additive and the second additive increases / decreases, the corresponding EMC content is reduced / increased at the same time), the percentage of other components in the electrolyte remains unchanged, the rest is the same as Example 1-1.

[0096] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Tables 1 and 2.

[0097] Table 1

[0098] In Table 1, “ / ” indicates no relevant parameters.

[0099] Table 2

[0100] In Table 2, “ / ” indicates no relevant parameters.

[0101] From Example 1-1 to Example 1-11, and Comparative Example 1-1 to Comparative Example 1-9, it can be seen that when the electrolyte without adding the first additive and the second additive, or only adding the first additive or the second additive, or the content of the first additive and the second additive is not within the scope of the present application, is applied to a lithium-ion battery, the lithium-ion battery cannot simultaneously meet the relatively excellent storage thickness expansion rate, storage capacity retention rate, storage capacity recovery rate, capacity after volume division, main exothermic peak temperature and heat release, resulting in poor overall effect of the lithium-ion battery. When the electrolyte to which the first additive and the second additive are simultaneously added is applied to a lithium-ion battery, and the content of the first additive and the second additive is limited to the scope of the present application, the lithium-ion battery has a lower storage thickness expansion rate and heat release, while the storage capacity retention rate, storage capacity recovery rate, capacity after volume division and main exothermic peak temperature are also relatively high, and the lithium-ion battery has the best overall effect. Figure 1 It can be seen that the main exothermic peak temperature of Examples 1-3 is 261.2° C. The above results illustrate that the first additive and the second additive are used in combination, and the contents of the first additive and the second additive are limited within the scope of this application. The first additive and the second additive work synergistically to improve the high temperature storage performance and thermal stability of the lithium ion battery.

[0102] From Example 2-1 to Example 2-9, it can be seen that the electrolyte with auxiliary salt added is applied to the lithium-ion battery, and the content of the auxiliary salt is limited within the scope of this application. The lithium-ion battery has a lower storage thickness expansion rate and heat release, and the storage capacity retention rate, storage capacity recovery rate, capacity after capacity division and main exothermic peak temperature are also relatively higher, and the overall effect of the lithium-ion battery is the best. The above results show that adding auxiliary salt to the electrolyte and limiting the content of the auxiliary salt to the scope of this application can make the electrolyte have higher ionic conductivity and good electrochemical stability, which can further improve the high temperature storage performance and thermal stability of the lithium-ion battery.

[0103] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0104] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. An electrolyte comprising a solvent, an additive and a lithium salt; the additive comprising a first additive and a second additive; The first additive is selected from the compound shown in formula I; ; in, R1 and R2 are each independently selected from unsubstituted or fluorine-substituted C1-C5 alkyl, unsubstituted or fluorine-substituted C2-C4 alkenyl; the mass percentage of the first additive in the electrolyte is A, 0.1%≤A≤8%; The second additive is selected from vinylene carbonate; the mass percentage of the second additive in the electrolyte is B, 0.1%≤B≤5%; The lithium salt includes lithium bis(fluorosulfonyl)imide; the mass percentage of the lithium bis(fluorosulfonyl)imide in the electrolyte is C1, 10%≤C1≤20%.

2. The electrolyte according to claim 1, characterized in that 0.1%≤A≤3%。 3. The electrolyte according to claim 1, characterized in that 1%≤B≤2.5%。 4. The electrolyte according to claim 1, characterized in that The compound represented by formula I is selected from at least one of the following compounds: 。 5. The electrolyte according to claim 1, characterized in that The lithium salt also includes an auxiliary salt; the auxiliary salt is selected from at least one of LiPF6, LiSO3CF3, LiBF4, LiN(SO2CF3)2, LiPO2F2, LiPF2(C2O4)2 and LiPF4C2O4; the mass percentage of the auxiliary salt in the electrolyte is C2, 0.1%≤C2≤2%.

6. The electrolyte according to claim 1, characterized in that The solvent is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate and methyl propyl carbonate; the mass percentage of the solvent in the electrolyte is D, 65%≤D≤89%. 7 . A lithium ion battery comprising a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte according to claim 1 .

8. The lithium-ion battery according to claim 7, characterized in that: The negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes graphite.

9. The lithium-ion battery according to claim 7, characterized in that: The positive electrode plate includes a positive electrode current collector and a positive electrode material layer arranged on at least one surface of the positive electrode current collector, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material is selected from at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium cobalt oxide and lithium-rich manganese-based materials.

10. The lithium ion battery according to claim 9, characterized in that: The positive electrode active material is selected from lithium iron phosphate.

Citation Information

Patent Citations

  • Lithium ion power battery and automobile using the same

    CN104466260A

  • 4.5 V high-voltage ternary lithium ion battery electrolyte and preparation method and application thereof

    CN116779970A

Cited By

  • Electrolyte, lithium ion battery and electronic equipment

    CN120413792A